Analisis Makna Cinta Abadi dalam Lirik Lagu Sekali Seumur Hidup Karya Lesti Kejora pada Kajian Semiotika Ferdinand de Saussure - Lidiya, Lidiya; Marini, Marini; Hagi Julio Salas (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Songs are a form of symbolic communication that serves to convey emotional, moral, and cultural messages through beautiful and artistic language. In the context of communication, songs are not merely entertainment, but also a medium for representing meaning that reflects the social and cultural values ​​of society. This study aims to analyze the meaning of eternal love in the lyrics of the song "Sekali Seumur Hidup" by Lesti Kejora using Ferdinand de Saussure's semiotic approach. This approach emphasizes the relationship between the signifier and the signified in the formation of meaning. The study uses a descriptive qualitative method through text analysis based on Saussure's concept of signs. Song lyrics serve as the primary data to explore the explicit and implicit meanings of the symbols used. The results of the analysis show that linguistic signs such as "mimpi", "raja dan ratu", "sekali selama hidup", and "pier mimpi" represent the value of true love. These symbols depict sincerity, loyalty, honesty, and the spirituality of love as a profound moral message. Communicatively, this song not only tells the story of a romantic relationship, but also emphasizes the universal meaning that true love is sacred, occurs once in a lifetime, and needs to be maintained with sincerity as a form of human emotional and spiritual expression.